2017
DOI: 10.1016/j.psychres.2017.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Problematic internet use among high school students: Prevalence, associated factors and gender differences

Abstract: This study aimed to measure the prevalence of Problematic Internet Use (PIU) among high school students and to identify factors associated with PIU underlining gender differences. The students filled a self-administered, anonymous questionnaire collecting information on demographic characteristics and patterns of Internet use. Multiple logistic regression analysis was performed to identify factors associated with PIU in the overall sample and by gender. Twenty-five schools and 2022 students participated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
60
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 68 publications
(29 reference statements)
10
60
1
Order By: Relevance
“…Internet addiction has been associated with a number of socio-demographic variables, time and patterns spent online, psychosocial factors, and comorbid symptoms/disorders (Carli et al 2013;Kuss et al 2017;Kuss et al 2014). Common predictors of IA include socio-demographic factors (e.g., age, gender, residence, relationship status), as well as other factors including sleep disturbance, lack of physical activity, and job status (Afrin et al 2017;Bener et al 2018;Bener and Bhugra 2013;Islam and Hossin 2016;Lai and Kwan 2017;Vigna-Taglianti et al 2017;Younes et al 2016). Generalized IA has also been associated with a wide variety of excessive online behaviors including using the internet for academic purposes, communicating via social networking sites, online gaming, accessing online movie and music sites, viewing online sexually explicit materials and pornography, online gambling, and online shopping (Bener et al 2018;Hoare et al 2017;Simcharoen et al 2018;Vigna-Taglianti et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internet addiction has been associated with a number of socio-demographic variables, time and patterns spent online, psychosocial factors, and comorbid symptoms/disorders (Carli et al 2013;Kuss et al 2017;Kuss et al 2014). Common predictors of IA include socio-demographic factors (e.g., age, gender, residence, relationship status), as well as other factors including sleep disturbance, lack of physical activity, and job status (Afrin et al 2017;Bener et al 2018;Bener and Bhugra 2013;Islam and Hossin 2016;Lai and Kwan 2017;Vigna-Taglianti et al 2017;Younes et al 2016). Generalized IA has also been associated with a wide variety of excessive online behaviors including using the internet for academic purposes, communicating via social networking sites, online gaming, accessing online movie and music sites, viewing online sexually explicit materials and pornography, online gambling, and online shopping (Bener et al 2018;Hoare et al 2017;Simcharoen et al 2018;Vigna-Taglianti et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Regression analysis of factors associated with excessive internet use undergraduates and postgraduates in Nigeria reported an IA prevalence rate of 3.3% (scoring 70-100 on the IAT), whereas 20.3% were reported as being at risk of IA (scoring 50-70 on the IAT)(Adiele and Olatokun 2014). A study in Italy reported an IA prevalence rate of 12.1% among high school students(Vigna-Taglianti et al 2017).…”
mentioning
confidence: 99%
“…Recent studies from other Asian countries have reported prevalence rates of 17% ('problematic internet use') in Delhi, India (N=6291 students; Balhara et al, 2018), 0.8% ('severe internet addiction') in Southern India (N=1763 medical students; Anand et al, 2018), 8.2% ('moderate internet addiction'; no severe cases) in Northern India (N=1721 doctors; Grover et al, 2019), 9.2% ('at-risk internet addiction'; no severe cases) in Southern India (N=310 workplace employees; Shrivastava et al, 2018) and 0.6% ('severe internet addiction') in Chiang Mai, Thailand (N=324 medical students; Simcharoen et al, 2018). Worldwide, rates of problematic internet use and/or IA have reported between 4.2% and 26.8% when utilizing different assessment instruments and cutoff scores (Vigna-Taglianti et al, 2017).…”
mentioning
confidence: 99%
“…In addition, the literature on internet addiction in recent years argues that, it is necessary to differentiate these dynamics by emphasizing that the increasing use of information technologies applications in education, training and business world in order to learn and develop as a requirement of information society cannot be considered within the scope of internet addiction (Griffiths, Kuss, Billieux, & Pontes, 2016) Therefore, students' use of information technology applications while doing homework or studying is not discussed in the context of internet addiction, on the contrary, it is regarded as the role behavior supporting the learning process of the member of information society. On the other hand, the difference in terms of internet addiction of students who stated that they do not take time to do homework, students who evaluate their academic success as bad and students who stated that they play computer games, can be supported with research related to adolescence behavior and adaptation problems as well as literature related to internet addiction and game addiction (Baltacı & Akpınar, 2011;Drennan, Kennedy, & Pisarski, 2005;Işık, 2010;Tandoğan & Orhan, 2007;Wu, 2013;Vigna-Taglianti, Brambilla, Priotto, Angelino, Cuomo, & Diecidue, 2017).…”
Section: Discussionmentioning
confidence: 91%